The Maithil Brahmans : an online ethnography (1999)
[Dt.:] Die Webseite von Carolyn Brown Heinz beschäftigt sich mit den Maithil Brahmanen in der geographischen Region Mithila im heutigen indischen Bundesstaat Bihar (teilweise auch Südnepal). Bereits im Ramayana findet dieses Königreich Erwähnung. Nach der Eroberung dieser Region durch die Afghanen im 13. Jahrhundert etablierte sich eine Brahmanen-Herrschaft (Darbhanga Raj). Carolyn Brown Heinz geht insbesondere auf die Genealogie dieser Maithil Brahmanen ein und grenzt sie gegenüber anderen Kastengemeinschaften in Mithila ab. Zudem informiert die Webseite auch über die Maithila-Kunst, bei der zu bestimmten festlichen Anlässen die Häuserwände und Mauern von den Frauen bemalt und verziert werden. - [Engl.:] This website, created by Carolyn Brown Heinz, contains informations about the caste of Maithil Brahmans and classical Maithil arts. Mithila is an ancient cultural region of North India lying between the lower ranges of the Himalayas and the Ganges River. The Nepal border cuts across the top fringe of this region. The Gandak and Kosi Rivers are rough western and eastern boundaries of Mithila. The Ramayana records a dynastic marriage between Prince Rama of Ayodhya and Sita, the daughter of Raja Janak of Mithila. The town of Janakpur, in the northern Nepali section of Mithila, is believed to be Janak's old capital. In the thirteenth century Mithila was invaded by Afghans, who deposed the Kshatriya ruler and placed a Maithil Brahman in control of land revenues over much of this region